Uncertainty of parents due to having children with cancer: A concept analysis - Ikeu Nurhidayah; Nani Nurhaeni; Allenidekania Allenidekania; Dewi Gayatri; Yeni Rustina (Belitung Nursing Journal, 2023)
Background: Parents of newly diagnosed cancer children often experience significant concerns about the implications of the diagnosis. They find themselves in challenging decision-making situations, navigating through uncertain conditions following the disclosure. Uncertainty is a prevailing issue in healthcare, yet its interpretation and application within the context of health and nursing practice exhibit multiple meanings and variations.   Objective: This study aimed to clarify the concept of parental uncertainty arising from having children with cancer.                                                              Methods: The concept analysis followed the steps outlined by Walker and Avant. A thorough literature search was conducted using the Embase, CINAHL, and MEDLINE databases to identify articles published between 1980 and 2022. Results: The literature search yielded 147 articles from various disciplines, including health, nursing, medicine, psycho-oncology, and management. After analysis, 20 articles were selected for inclusion. This study identified four key attributes of parental uncertainty associated with having a child with cancer: (1) emotional disturbance, (2) unpredictability, (3) insufficient information, and (4) problems with decision-making. The antecedents of parental uncertainty encompassed the complexity of the disease, the diagnostic and treatment processes, the hospital environment, communication, and support from credible authorities. The consequences of parental uncertainty included the pursuit of new information, parental adaptability to their role, and parental distress. Conclusion: Understanding the four attributes of parental uncertainty, along with their antecedents and consequences, can facilitate the future development and operational translation of the concept of uncertainty in nursing practice. This concept is valuable in the evidence-based provision of nursing care to parents of children with cancer, enabling comprehensive recognition and assessment of parental uncertainty and the implementation of appropriate interventions that are sensitive to parental experiences. Ultimately, this approach promotes the adaptation of both the child and the parent.